Refugia Plant Pest and Disease Management in Wolasi, South Konawe Wolasi - Rahayu Rahayu Mallarangeng; Muhammad Taufik Muhayang; M Tufaila H; Rachmawati Hasid Hasid (JURNAL KARYA PENGABDIAN, 2022)
Exposure to synthetic chemicals for plant pest organisms (OPT) is the main choice for farmers. One alternative pest control is planting refugia plants. Refugia plants can attract beneficial insects and antagonistic agents to come to the plant. Furthermore, it can control the pest population naturally. The purpose of the service is technical guidance on the application of refugia technology in cayenne pepper cultivation. The method used is technical guidance and the manufacture of demonstration plots of chili plants using refugia plants. The comparator is the chili plant which is not refugia. The results showed that the application of synthetic chemicals was lower in chili plants that plant were given refugia than those that were not. The average growth height and the number of pepper branches that were given refugia were higher, and the visit of insect pests was lower than the control. Partners accept the refugia technology because it reduces the number of applications of synthetic chemical pesticides